Solubility Analysis of Endodontic Irrigants within the Root Canal System: A Computational Modeling Approach - Dede Arsista; Irsandy Idris; Ridhayani Hatta (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Endodontic irrigation solutions play an important role in the success of root canal treatment because they are able to clean debris, dissolve necrotic tissue, and reduce the number of bacteria. However, the effectiveness of irrigation materials can be affected by temperature factors during clinical procedures. Purpose: This study aims to analyse the effect of temperature on the solubility of several endodontic irrigation materials using the COSMO-RS computational modelling method as a predictive approach. Methods: This study is an analytical observational study endodontic irrigation). Chemical structure data were obtained from the PubChem database and analysed using COSMO-RS software Results: The results showed that increasing the temperature from 36oC to 37oC significantly increased the solubility of all irrigation materials. CHX had the highest solubility, followed by EDTA and MTAD. Conclusion: Increasing temperature has been shown to increase the solubility of endodontic irrigants, while the COSMO-RS computational method effectively predicts solubility before laboratory testing.